Normally we charge $1.00 for this answer

Today, you can get it FOR FREE if you

g+1, Follow or Like, us

Show me how to post my homework

Just do my homework!

  • HTML tags will be transformed to conform to HTML standards.
  • Add rel="nofollow" to external links
Question
Submitted by jjackson11677 on Sun, 2012-03-04 17:54
due date not specified
answered 2 time(s)
jjackson11677 bought 0 out of 1 answered question(s)
one anonymous student showed interest

2x+3y+7z=13 3x+2y-5z=-22 5x+7y-3z=-28

2x+3y+7z=13 3x+2y-5z=-22 5x+7y-3z=-28

Answer
Submitted by kodang on Mon, 2012-03-05 07:42
teacher rated 0 times
0
price: $5.00

Solution by Cramer's rule

body preview (19 words)

To solve xxxx equation xxx be xxxx Cramer's xxxxx

x attach xxx xxxxxxxx in xxx xxxx of x xxxxx

file1.doc preview (189 words)

xxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxx

To solve xxx above equation xxx xx used Cramer's Rule.

AX x B

x is xxx xxxxxxxxxxx xxxxxxxx

X is x xxxxxx vector.

x xx x vector.

xxx xxxxxxxx xx xx x xx x A

For xxxx case xxxxxxxx

xxx

B = xxxxx xxxxxxxxx xxxxxxxx xxxx xxx equation.

xxxx xxxxxxxx by xxxxxxxxx xxx first column xx the xxxxxx A xx xxx constant vector x

Ay = xxxxxxxx by xxxxxxxxx xxx second column xx the matrix A xx the constant vector B

xxxx xxxxxxxx xx xxxxxxxxx xxx third column of the xxxxxx A by xxx xxxxxxxx xxxxxx B

The next xxxx xx xx calculate xxx xxxxxxxxxxx xx xxxx xxxxxxx

xxxx = x xx

|Ax| = x xxxx

|Ay| = x -174

|Az| = x 261

xxxxxxxxxxx xxx value xx x, y xxx x can be xxxxxxxxxxx

xxxx |Ax| / |A|

= -87 / xxx

xxx xxx

xxxx |Ay| x xxxx

= -174 x 87

xxx -2

z = xxxx x xxxx

= xxx x xxx

Thus xxxxxxxx xxxxxxxx xxx y, z) = xxxx xxxxxx

Note:

If there are less obvious, xxx xxx xxxxxxxxxxx xxxx pm xx xxxx

xxxxx you.

the coefficient of x

the xxxxxxxxxxx of y

xxx xxxxxxxxxxx of z

_1392475990.unknown

xxxxxxxxxxxxxxxxxxx

xxxxxxxxxxxxxxxxxxx

xxxxxxxxxxxxxxxxxxx

_1392476204.unknown

_1392476054.unknown

xxxxxxxxxxxxxxxxxxx

_1392475826.unknown

_1392475339.unknown


Buy this answer

Try it before you buy it
Check plagiarism for $2.00

Answer
Submitted by shormi.dhaka on Mon, 2012-03-05 00:18
teacher rated 0 times
0
price: $1.00

The solution is (x,y,z) = (-1,-2,3).

body preview (317 words)

2x+3y+7z = 13

xxxxxxxx = -22

xxxxxxxx x xxx

1. Pick a letter xx eliminate and xxx equations that xxxxxxx xxxx xxxxxxx

x will arbitrarily pick the letter y xx xxxxxxxxx and I xxxx arbitrarily

pick the xxxxxxxxxx

3x+2y-5z = xxx

xxxxxxxx = -28

to eliminate x from.

xxxxx the xxxxxxxxxxxx of x xxx x xxx 7, xxxxxxxx the first

xxxxxxxx xxxxxxx xx xx xxx the second xxx xxxxxxx xx x xx

they will have coefficients xxxx will cancel when equals are

xxxxx to xxxxxxx

xxxxxxxxxxxx x xxx

xxxxxxxx 6z = -56

-------------------

-11x +29z x 98

2. Next, eliminate that same letter from one xx xxxxx xxxxxxxx

xxx the equation you xxx not use in xxxx 1.

I did not xxx

2x+3y+7z = xx

xx xxxx 1. I will use it with

xxxxxxxx x xxx

to eliminate the xxxx xxxxxx xx

3x+2y-5z = xxx

2x+3y+7z x 13

Multiply the first xxx xxxxxxx xx xx xxx xxx xxxxxx

xxx xxxxxxx by 2:

xxxxxxxxxx x xx

4x+6y+14z = xx

xxxxxxxxxxxxxxx

xxx xxxx x xx

xx xxx you have x xxxxxx xx xxxx two equations xx two letters:

-11x+29z x 98

- - - more text follows - - -


Buy this answer

Try it before you buy it
Check plagiarism for $2.00